2017
DOI: 10.4012/dmj.2016-255
|View full text |Cite
|
Sign up to set email alerts
|

Micro computed tomography evaluation of the Self-adjusting file and ProTaper Universal system on curved mandibular molars

Abstract: The aim of this investigation was to compare the cleaning and shaping efficiency of Self-adjusting file and Protaper, and to assess the correlation between root canal curvature and working time in mandibular molars using micro-computed tomography. Twenty extracted mandibular molars instrumented with Protaper and Self-adjusting file and the total working time was measured in mesial canals. The changes in canal volume, surface area and structure model index, transportation, uninstrumented area and the correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…4,27,36,41,44,47,102,104 In addition, it is also possible to quantify the percentage of root canal walls touched and not touched by instruments. The touch or action of the instrument on the canal walls and the changes in volume and SMI are the parameters most used (68.85%) to evaluate the preparation by means of micro-CT. 4,11,15,42,47,57,62,83,96,102,103,105 The change in canal volume is related to the effects of biomechanical preparation on dentin removal, 7,25,44,83,132,133 showing that the volume increase after preparation is proportionally higher in the cervical and middle third than in the apical and can be attributed to the cervical preparation 7,32,33,84 and to the greater taper of the instruments in the cervical region. 11,47 Clinically, the increase in canal volume in the cervical third can mean the improvement of the reach of irrigating solutions in the apical third, or that the apical mechanical debridement was not as effective as cervical 7,12 (Figure 3).…”
Section: Antomical Aspects That Influence the Sample Selection And Bimentioning
confidence: 99%
See 2 more Smart Citations
“…4,27,36,41,44,47,102,104 In addition, it is also possible to quantify the percentage of root canal walls touched and not touched by instruments. The touch or action of the instrument on the canal walls and the changes in volume and SMI are the parameters most used (68.85%) to evaluate the preparation by means of micro-CT. 4,11,15,42,47,57,62,83,96,102,103,105 The change in canal volume is related to the effects of biomechanical preparation on dentin removal, 7,25,44,83,132,133 showing that the volume increase after preparation is proportionally higher in the cervical and middle third than in the apical and can be attributed to the cervical preparation 7,32,33,84 and to the greater taper of the instruments in the cervical region. 11,47 Clinically, the increase in canal volume in the cervical third can mean the improvement of the reach of irrigating solutions in the apical third, or that the apical mechanical debridement was not as effective as cervical 7,12 (Figure 3).…”
Section: Antomical Aspects That Influence the Sample Selection And Bimentioning
confidence: 99%
“…Regarding the thirds, all systems evaluated in this literature review showed root canal transportation mainly at the apical third in mesial root canals with moderate curvature. 7,9,12,13,14,25,27,31,37,38,39,44,45,47,58,59,68,79,81,84,86,87,88,90,93,94,95,96,98,101,102,103,105,106 Regarding kinematics of the instruments, it was possible to verify that the instruments that act in vibratory mode presented less variations of transport and centralization considering the entire root canal (0.03 mm-0.14 mm), 84 followed by the instruments in adaptive (0.01 mm-0.058 mm), 47,58, , continuous (0.00 mm-0.62 mm), 14,27 and reciprocating action (0.04 mm-0.48 mm). 37,45 According to Wu et al, 134 transportation in the apical third more than 0.3 mm could negatively affect the obturation sealing, 38,86,134 and the values found in this review have not exceeded this critical limit in this root third.…”
Section: Expression Of Canal Transportation and Centering Ability Durmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the orientation in which the samples were evaluated, a positive value for the alteration of centroid X meant an alteration in the buccal direction, centroid Y in the mesial direction, and centroid Z in the apical direction [26]. The transportation was investigated by calculating the vectorial translocation of all sections' X, Y, and Z coordinate values using the following formula, where "a" is after and "b" is before preparation: (Xa − Xb) 2 + (Ya − Yb) 2 + (Za − Zb) 2 [27].…”
Section: Microct Evaluationmentioning
confidence: 99%